Training on Infrastructure Finance in Public Private Partnership Projects - World Bank (Washington, DC, 2013)
Cambridge Economic Policy Associates (CEPA) was selected to provide a training course on infrastructure finance for the State Bank of Pakistan (SBP), co-funded by the World Bank. This final report provides: an overview of the final course provided (section two); a summary of the participants (section three); the results of two assessments (one of the learning arising from the training and one relating to the provision and coverage of the course - sections four and five); and some conclusions and next steps (section six). The course through plenary sessions, case studies and exercises, culminating in a morning long computer based exercise on the final day, evaluating a Public Private Partnership (PPP) project. Pakistan case studies learning lessons from relevant case studies can be helpful, although work would be required to develop the case studies outside of the power sector. This report has summarized the results of the course provided by CEPA during July 2010. Finally, the support of the SBP and the facilities available at the Learning and Resource Centre (LRC) helped make the course a success.